(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: To assess the effectiveness of nonfluoroscopically guided caudal epidural injection of local anesthetic with steroid in patients with disc herniation and moderate spinal canal stenosis. Materials and methods: A prospective study was conducted in Physical Medicine & Rehabilitation Department, Dhaka Medical College Hospital, Dhaka from1.7.2017 to 30.6.2018. Thirty patients were diagnosed as PLID with moderate spinal canal stenosis clinically as well as confirmed by MRI lumbosacral spine to patients received 2 weeks traditional physiotherapy but improvement was not satisfactory. Neurosurgery consultation was taken, but patient refused to do operation. After taking written consent, Injection Triamcinolone acetonide 80 mg was given each patient through caudal epidural route. Patients were assessed on three parameters (VAS, SLR, Walking distance) before intervention and following injection at 1st,4th,12th week follow up. Results: There was obvious improvement found following intervention in all three parameters and all of these were statistically highly significant up to 12thweek follow up. Conclusion: Nonfluoroscopically guided caudal epidural injection of local anesthetic with steroid in patients with disc herniation and moderate spinal canal stenosismay be an effective treatment and may be tried before surgery Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 41-44